Violence Against Women in Bangladesh and How We Can Prevent it? - Bint-E-Basar, Kaniz Tania; Al-Amin, Dewan Md.; Mostofa, Md. (American International Journal of Social Science Research, 2018)
This paper examines Violence against women (VAW) takes place in different sectors in Bangladesh. There are various types of violence in our country i.e. physical, sexual, domestic violence, killing, rape etc. Socio-Economic aspect also plays a pivotal role in violence against women. There are some common features of VAW like polygamy, extra-marital or pre-marital relations, lack of social and economic security, lack of proper education and cybercrime. Unemployment is also one of the main reasons of VAW in Bangladesh. Prevention measures should be taken by family, society and also by the state machine to prevent VAW. Implementation of domestic laws of VAW and monitoring system and social awareness will be the effective measures to prevent this criminal activity from the society and from the state.